A lead-free ferroelectric Bi0.5Na0.5TiO3 based flexible, lightweight nanogenerator for motion monitoring applications. Issue 11 (21st September 2020) - Maria Joseph Raj, Nirmal Prashanth; KS, Abisegapriyan; Khandelwal, Gaurav; Alluri, Nagamalleswara Rao; Kim, Sang-Jae
Abstract : A lead-free ferroelectric system Bi0.5 Na0.5 TiO3 implemented in a flexible, lightweight piezoelectric nanogenerator for energy harvesting and self-powered monitoring applications. Abstract : The demand for wearable devices has generated intense interest from both industrial scientists and academic researchers. Wearable technology devices must be small, lightweight, and flexible. We propose wearable devices incorporating ferroelectric Bi0.5 Na0.5 TiO3 nanoparticles (BNT NPs) for motion monitoring and energy harvesting. BNT NPs were prepared using an inexpensive approach, and their fundamental material properties were evaluated by X-ray diffraction analyses, Raman spectroscopy, and scanning electron microscopy. The dielectric, ferroelectric, and piezoelectric properties of our BNT system were characterized: it exhibited a dielectric constant/loss of 325/0.039 at 1 kHz with a depolarization temperature of ∼205 °C. A maximum ferroelectric remnant polarization ( P r ) of 34 μC cm −2 at 1 Hz was obtained with a piezoelectric coefficient of 79 pC N −1 . Polycaprolactone was used as a matrix to fabricate flexible composite films (PBNT CFs) containing different amounts of BNT NPs. Optimized composites containing 50% BNT based piezoelectric nanogenerators (CPNGs) generated a maximum electrical response of 22 V and 140 nA, and an instantaneous power density of 3.95 mW m −2 in response to an applied mechanical force of 6 N @ 1 m s −2 . The PBNT CPNGs were used to charge capacitors and were analyzed in terms of stability, poling, and acceleration-dependent energy harvesting performance. Motion monitoring and energy harvesting in a wearable device were demonstrated while walking, with a heel strike motion yielding 40 V and 220 nA.